Enoxaparin for the Prevention of Preeclampsia and Intrauterine Growth Restriction in Women With a History: A Randomized Trial. Issue 4 (December 2017) - Groom, K.M.; McCowan, L.M.; Mackay, L.K.; Lee, A.C.; Said, J.M.; Kane, S.C.; Walker, S.P.; van Mens, T.E.; Hannan, N.J.; Tong, S.; Chamley, L.W.; Stone, P.R.; et al.
Abstract : ( Am J Obstet Gynecol. 2017;216(3):296.e1–296.e14) Preeclampsia and intrauterine growth restriction (IUGR) are both placental diseases and major causes of perinatal and maternal morbidity and mortality. The most commonly used risk predictor for both IUGR and preeclampsia is obstetric history, and women are more significantly at risk if the condition occurred early in pregnancy and was severe. Previous studies have shown aspirin and calcium can significantly reduce the incidence of preeclampsia, and results from trials for heparin and low-molecular-weight-heparin (LMWH) have yielded conflicting results. This multicenter randomized controlled trial aimed to assess the use of LMWH for the prevention of small for gestational age (SGA) infants and preeclampsia in women with a history of these conditions.